A „Kegyetlenül szomorú kötelesség”: A TRIANONI BÉKEDIKTÁTUM BECIKKELYEZÉSE 2. 1920. OKTÓBER 26. – 1920. NOVEMBER 12. - Vizi, László Tamás (Közép-Európai Közlemények, 2019)
This study is a continuation of the previously published paper in the Central European Publications No. 35, which presented the political controversies about the codifing of the Trianon Peace Treaty and that massive pressure exerted on Hungary by the great powers for the purpose of making it. The antecedents of the ratification process and the entry into force of the peace treaty were the result of more than one year’s process. The study describes the period from 4th June 1920, the signing of the peace treaty, till 26th October 1920, the referral of the peace treaty to the National Assembly. The paper presents in details the content of the ratification bill and its justification. It analyzes the content of the letter in which the Hungarian party informed the ambassadors’ commission on the submission of the bill. At the same time, asking the great powers to call on the governments of neighboring countries to respect the minority rights of millions of Hungarians, who were attached to them as a result of the peace treaty. The study describes the French Prime Minister’s response to the Hungarian letter, and follows up with the further developments of the ratification of the Trianon Peace Treaty, presents the leading political opinions and the decisions of the National Assembly that determined the Hungarian political life and affected the public’s everydays, until the beginning of the ratification debate of the National Assembly, from 13rd November 1920.